ANALISIS PENGARUH BIMBINGAN KONSELING BERBASIS PENDIDIKAN ISLAM DALAM MEREDUKSI PERILAKU BULLYING PADA SISWA - Putri, Rasikha Aulia; Safitri, Anggie Resa; Litasya, Zahara; Yulianti, Yulianti; Awaliyah, Iftitah; Nurika, Haliza; Khairunnisa, Hernita (Universitas Islam Kalimantan Muhammad Arsyad Al-Banjari Banjarmasin, 2024)
In Indonesia, the prevalence of bullying behavior among students reaches a fairly high level, in various forms such as taunts, insults, and beatings. Handling bullying behavior requires an active role from the school, one of which is through counseling guidance services. The objectives of Islamic guidance include helping individuals solve problems, preventing problems from arising, and guiding individuals in carrying out the teachings of Islam. Low empathy is identified as another contributor to bullying behavior, and Islamic guidance is considered an important effort in creating quality students. Future research can further explore the implementation of guidance and counseling programs in collaboration with religious and Islamic education. Incorporating the experiences of students, teachers, counselors, and parents will provide valuable insights to improve the effectiveness of these programs. Thus, it is hoped that this research can provide a more comprehensive view in addressing the problem of bullying behavior among students.